Effect of growth regulating chemicals on flowering, corm production and post harvest life of gladiolus (Gladiolus grandiflorus) cv. Punjab Dawn in Bay Islands - BASKARAN, V; ABIRAMI, K; SIMHACHALAM, P (The Indian Journal of Agricultural Sciences, 2017)
Field experiment was conducted for two consecutive seasons during November to April 2013-14 and 2014-15 in the Division of Horticulture and Forestry, Central Island Agricultural Research Institute, Port Blair to study the effect of plant growth regulators on gladiolus [Gladiolus grandiflorus Hort.] cv. Punjab Dawn. The results obtained showed that the growth, flowering and corm characters were significantly influenced by the application of growth regulators at different concentrations. Earliness in corm sprouting was observed by GA3 @ 250 ppm (8.7 days). Maximum number of leaves/plant and plant height were recorded in GA3 @ 750 ppm (9.6 and 93.6cm respectively). More number of shoots/corm was observed in the treatment BA @ 75 ppm (4.0). With respect to flower characters, early spike emergence and maximum duration of the spike were recorded by GA3 @ 500 ppm (46.7 days and 16.2 days respectively). Maximum spike length, rachis length, number of florets/spike and floret size (74 cm, 50.2 cm, 14.3 and 11.4 cm respectively) were recorded by GA3 @ 750 ppm. With regard to post harvest studies, maximum longevity of opened floret and vase life of cut spike (3.9 days and 14.2 days respectively) were recorded by GA3 @ 750 ppm .With regard to the corm characters, maximum number of corms and cormels/plant were observed in BA @ 100 ppm (3.7 and 11.8 respectively). Weight of single corm, weight of corms/plant, size of single corm, volume of single corm and propagation coefficient were also maximum in GA3 @ 750 ppm (70.9 g, 169.3 g, 7.0 cm, 79.5 cm3 and 348.3% respectively).